A Case Series of Malignant Otitis Externa Mimicking Malignancy - Selvamalar, Vengathajalam; Othman, Nik Adilah Nik; Daud, Mohd Khairi (Acta medica (Hradec Kralove), 2021)
Malignant otitis externa is an inflammation of the external auditory canal with preceding osteomyelitis of the temporal bone and the adjacent structures that could be potentially lethal. Malignant otitis externa may present with cranial nerve involvements and massive spread of disease mimicking nasopharyngeal carcinoma or any other malignancies on imaging. Two elderly patients who presented with severe otalgia and significant facial nerve palsy and lower cranial nerve palsies showing extensive spread of disease are reported in this case series. They both had resolution of disease after a prolonged course of antibiotics and cortical mastoidectomy for disease clearance in one of them.
Keywords: Facial Paralysis; malignant otitis externa; Magnetic Resonance Imaging; diferenciální diagnóza; Female; biologické markery; Biomarkers; ženské pohlaví; Tomography, X-Ray Computed; Mastoidectomy; lidé; Otitis Externa; Anti-Bacterial Agents; magnetická rezonanční tomografie; otitis externa; faciální paralýza; Diagnosis, Differential; Humans; osteomyelitis; Pseudomonas aeruginosa; kombinovaná farmakoterapie; lidé středního věku; antibakteriální látky; mastoidektomie; cranial nerves palsies; Middle Aged; Drug Therapy, Combination; počítačová rentgenová tomografie